A Analysis Of Occupational Safety and Health Promotion Implementation On Employees At Pt. Siantar Ice Factory - RAMAWATI, NURVITA; Barita Aritonang; Sri Ulina (Fakultas Kesehatan Masyarakat Institut Kesehatan Medistra Lubuk Pakam, 2024)
Background: Mortality rates over time can describe the state and development of public health. Maternal Mortality Rate is one of the important indicators in determining the health of the community. Improving the health status of mothers and children (KIA) is still one of the main priorities in health development in Indonesia, due to the still high Maternal Mortality Rate (MMR) and Infant Mortality Rate (IMR) in Indonesia.Objectives: o analyze the implementation of occupational safety and health promotion for Employees at PT. Pabrik Es Siantar.Research method: ualitative method with a qualitative descriptive approach that does not provide treatment to research subjects with qualitative research that aims to explore a problem with detailed limitations, as well as in-depth data collection.Results: The number of informants in this study was 7 people. Data collection was carried out using an in-depth interview method equipped with a voice recorder to 7 informants. Based on the results of the research conducted, the results of the analysis showed that there were still many employees who worked but still ignored the importance of K3 such as not using PPE while working which is one of the things that must be worn while working. this can endanger workers because the risk of work accidents while working is very high, including in the production section.Conclusion: promotion and occupational safety and health facilities are quite good, only employee awareness is still lacking. Suggestions that can be given are Suggestions that can be given are to carry out supervision of all work processes that are further improved so that workers do things outside of work procedures, and to equip personal protective equipment in each division according to their work.